2018
DOI: 10.1002/ijc.32072
|View full text |Cite
|
Sign up to set email alerts
|

Loss of KDM6A characterizes a poor prognostic subtype of human pancreatic cancer and potentiates HDAC inhibitor lethality

Abstract: Although genomic analysis have recently discovered the malignant subtype of human pancreatic ductal adenocarcinoma (PDAC) characterized by frequent mutations of histone demethylase KDM6A, the biological and molecular roles still remain obscure. We herein elucidated the clinical and biological impacts of KDM6A deficiency on human PDAC and identified the therapeutic potential by pathological and molecular evaluation. Immunohistochemical analysis suggested that loss of KDM6A in cancerous tissues was an independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 34 publications
2
32
1
1
Order By: Relevance
“…In particular, we found that ARID1A-mutant cells are significantly more sensitive to NVP-AUY922 compared to Author Manuscript Published OnlineFirst on November 6, 2020; DOI: 10.1158/0008-5472. like KDM6A (33), though other unknown mechanisms may also be at play. Loss of ARID1A expression is typically induced by nonsense mutations, insertions, and deletions in the genecoding region, which lead to mRNA decay or sequence truncation (14).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that ARID1A-mutant cells are significantly more sensitive to NVP-AUY922 compared to Author Manuscript Published OnlineFirst on November 6, 2020; DOI: 10.1158/0008-5472. like KDM6A (33), though other unknown mechanisms may also be at play. Loss of ARID1A expression is typically induced by nonsense mutations, insertions, and deletions in the genecoding region, which lead to mRNA decay or sequence truncation (14).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, KDM6A mutations suppress cell proliferation by activating retinoblastoma protein-related genes, which suggests that KDM6A serves as a putative tumor suppressor (12). Furthermore, the biological function of KDM6A in a number of malignancies, including bladder and lung cancer, as well as pancreatic ductal adenocarcinoma, has been reported (13)(14)(15)(16). However, the cellular and molecular mechanisms underlying KDM6A in HCC are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…KDM6A (also known as UTX) functions as a histone H3K27 demethylase, removing the repressive H3K27 methylation mark to foster transcriptional gene activation (van Haaften et al 2009). There is strong evidence that loss-of-function mutations in KDM6A, an established tumor-suppressor gene, play a role in cancer progression (Watanabe et al 2018). Sequencing efforts of both hematologic and nonhematologic malignancies in humans support this notion (van Haaften et al 2009;Van der Meulen et al 2015;Waddell et al 2015;Chakravarty et al 2017;Gozdecka et al 2018).…”
Section: Characteristics Of the Key Mutated Genesmentioning
confidence: 99%